Learning English in Early Childhood Education with Augmented Reality: Design, Production, and Evaluation of the "Wordtastic Kids" App - Aleyda Mamani-Calapuja; Victoria Laura-Revilla; Alejandra Hurtado-Mazeyra; Carmen Llorente-Cejudo (MDPI AG, 2023)
The pedagogical use of AR for language learning in early childhood education is focusing attention on the didactic potential that these resources present at such early ages. The aim of this study was to develop and assess the "Wordtastic Kids" Application (APP) in order to: (a) design, produce, and evaluate a new contextualized AR application for learning English in early childhood education; and (b) know the academic performance of early childhood education students towards learning English using an AR application. The methodology was based on the design of materials and the subsequent realization of the pre-test/post-test evaluation to determine the academic performance of the students. The results show a general increase in the scores obtained in all the pre-test and post-test categories that were addressed using the Wordtastic Kids Application, which proves to be a tool that improves the learning of English vocabulary in pre-school children. Therefore, it can be concluded that AR can be useful for complementing traditional vocabulary learning in children. However, it is important to note that the successful implementation of AR will depend on several factors, such as adequate teacher preparation, the quality of AR content, and the ability of children to interact with technology effectively.